2017
DOI: 10.1038/s41598-017-11386-8
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange Bias of LaMnO3/LaNiO3 Superlattices Grown along Different Orientations

Abstract: With the goal of observing and explaining the unexpected exchange bias effect in paramagnetic LaNiO3-based superlattices, a wide range of theoretical and experimental research has been published. Within the scope of this work, we have grown high-quality epitaxial LaMnO3(n)-LaNiO3(n) (LMO/LNO) superlattices (SLs) along (001)-, (110)-, and (111)-oriented SrTiO3 substrates. The exchange bias effect is observed in all cases, regardless of growth orientation of the LMO/LNO SLs. As a result of a combination of a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…It is largest for the maximally strained samples (columnar ST14 and nanomaze LA14). The spectral weight of feature B is related to the hybridization of oxygen 2p with transition metal 3d orbitals and charge transfer effects from Mn to Ni as previously reported for the Ni 3+ systems LaMnO 3 ( n )–LaNiO 3 ( n ) and La 0.7 Sr 0.3 MnO 3 /LaNiO 3 superlattice heterostructures. However, in the present samples, we exclude the possibility of charge transfer from Mn to Ni, or vice versa, as the valence state of Ni is found to be +2 for all the samples as discussed above.…”
Section: Resultssupporting
confidence: 69%
“…It is largest for the maximally strained samples (columnar ST14 and nanomaze LA14). The spectral weight of feature B is related to the hybridization of oxygen 2p with transition metal 3d orbitals and charge transfer effects from Mn to Ni as previously reported for the Ni 3+ systems LaMnO 3 ( n )–LaNiO 3 ( n ) and La 0.7 Sr 0.3 MnO 3 /LaNiO 3 superlattice heterostructures. However, in the present samples, we exclude the possibility of charge transfer from Mn to Ni, or vice versa, as the valence state of Ni is found to be +2 for all the samples as discussed above.…”
Section: Resultssupporting
confidence: 69%
“…Because the LMO layer is an A-type AFM insulator and the LNO layer is a PM metal, the EB observed in this SL is different from what occurs in traditional ferromagnetic/AFM systems. The reasons why this unexpected EB was observed in the (111) direction and not in the (001) orientation have been studied by detecting the interfacial charge and spin via element-specific X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD). Piamonteze et al compared two different orientations and found a larger charge transfer for (111) SLs compared to (001), which further confirms the origin of the EB effect from (111) SLs rather than (001). However, Hoffman et al found a considerable charge transfer between Ni and Mn in the (001) stacking, although the EB had never been mentioned in the literature .…”
Section: Introductioncontrasting
confidence: 80%
“…Thus, we will be able to conclude that the exchange bias is related to the onset of an AFM ordering of NNO, governed by the exchange coupling between the constituent antiferromagnetic Ni 3+ and Nd ions, and the ferromagnetic LSMO layer that shares a common interface with the NNO layer. The interfacial magnetic frustration will be inferred from the occurrence of mixed ferromagnetic and antiferromagnetic ordering, supporting also possible spin-glass states formed at the LSMO/LNO [12,25], LaMnO 3 /LNO [36][37][38], and LSMO/SrMnO 3 interfaces [39].…”
Section: Introductionmentioning
confidence: 65%